Cardiac rupture after ST elevation myocardial infarction – a decade's experience of a tertiary cardiology centre. (3rd October 2022) - Margineanu, C; Antohi, E L; Bubenek, S; Carp, A; Deleanu, D; Filipescu, D; Filipescu, R; Geavlete, O D; Iliescu, V; Radulescu, B; Stiru, O; Stoica, E; et al.
Abstract:  : Mechanical complications post ST elevation myocardial infarction (STEMI) are life-threating events, that require rapid recognition and appropriate management. Clinical diagnosis, considering high index of suspicion and bedside echocardiography should be considered in all STEMI patients Despite the overall decrease of the incidence of cardiac rupture (CR) secondary to STEMI in context of early revascularization and the wide availability of primary PCI, CR has still an unacceptable high mortality. Purpose: To provide demographic, clinical, management and prognostic data associated to cardiac rupture from a tertiary centre of cardiology in Romania and to better describe in-hospital trajectory. The primary endpoint was defined as the incidence of CR and secondary endpoints were rate of surgical interventions, in-hospital mortality rate at 24 hours and after 24 hours during index hospitalization. Methods: The analysis of the electronic medical records retrospectively identified 7703 patients admitted for STEMI between 01 Jan 2011 and 31 Dec 2020. A database consisting of demographic data, medical history, cv and non-cv comorbidities, in-hospital management were recorded using an UiPath robotic process automation (RPA) technology. Characteristics of the patients +/− CR were compared, and data analysis was performed using SPSS 26 Ed. Results: Of a total number of 7703 consecutive STEMI patients, CR has been identified in 185 patients (mean incidence of 2.4%). The annual rates for CR incidence remained stable during the past decade (Figure 1). Patients with CR were older compared with non-CR (71.6±10.2 vs 61.47±12.8 years; p<0.001) and more commonly female (3.92% vs 1.78% males, p=0.04). The CR patients had more comorbidities and CV risk factors – HTN, smoker status, DLP, more AF, CKD, obesity and chronic cognitive deficit (p<0.05), but not DM (p=0.6). Among the CR group patients, anterior MI was the frequent localisation (52%), followed by inferior MI (17%), infero-lateral (23%) and RV involvement MI (6.4%). According to the type of the mechanical complication, patients developed free wall rupture (50% of cases), 39% IVS rupture and 11% papillary muscle was involved; A number of 50 patients (27%), benefited from emergent cardiac surgery and 31.3% of CR patients received mechanical circulatory support. The overall STEMI mortality in the first 24-hours was 1.84% and in most of these patients the main cause of death was related to CR (31%). Overall total in-hospital mortality was 8.08% (6.5% non-CR group vs. 70.8% the CR group – Figure 1). Conclusions: The study presents the epidemiological characteristics of CR complicating STEMI in the largest tertiary cardiovascular hospital in Romania. We have identified a stable trend for the incidence of CR incidence among patients with STEMI. In spite of the high rate of cardiac surgery and MCS, in-hospital mortality remains very high, particularly in the first 24 h since admission Funding Acknowledgement: Type of funding sources: None.